1991
DOI: 10.1111/j.1365-4362.1991.tb05884.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Squamous Cell Carcinoma with Interferon

Abstract: Human natural leukocytic interferon and recombinant HulFN alpha 2c can be used in the therapy of squamous cell carcinoma. The duration of treatment was 3-6 weeks. A single dose was 400,000-5,000,000 units given weekly for 3-6 weeks. Clinically and histologically 19 of 32 patients were cured and tumor cells were not found in the material taken after interferon treatment for the second biopsy. In ten patients tumor size was reduced 25-90%, and in three patients tumor size was not reduced according to clinical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The efficacy of alpha interferon is well established regarding its activity against squamous cell carcinoma of the skin, in which it induces apoptosis 18 . Ikiċ et al 19,20 were the first to use the intratumoral application in the treatment of squamous cell carcinoma, demonstrating a reduction and even disappearance of this tumor. Jakacki et al 21 were the first to use systemic alpha interferon in the treatment of recurring craniopharyngiomas and those that did not respond to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of alpha interferon is well established regarding its activity against squamous cell carcinoma of the skin, in which it induces apoptosis 18 . Ikiċ et al 19,20 were the first to use the intratumoral application in the treatment of squamous cell carcinoma, demonstrating a reduction and even disappearance of this tumor. Jakacki et al 21 were the first to use systemic alpha interferon in the treatment of recurring craniopharyngiomas and those that did not respond to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12 Many authors have noted that when a lesion appears to be clinically resolved, there is histologic resolution of the tumor as well. 2,[13][14][15] It appears that a 16-week posttreatment period is required for adequate assessment of IFNa-2b efficacy. Histologic assessment, if any, should be deferred until this point.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have observed that some lesions with partial regression at 8 weeks after treatment progressed to achieve a histologic cure (without further treatment) at 16 weeks 12 . Many authors have noted that when a lesion appears to be clinically resolved, there is histologic resolution of the tumor as well 2,13–15 . It appears that a 16‐week posttreatment period is required for adequate assessment of IFNα‐2b efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Этот режим дозирования использовался также в исследовании L.Edwards и соавт. в терапии инвазивного ПКРК и плоскоклеточного рака in situ с эффективностью 96,2% и 97%, соответственно [148]. L Anasagasti-Angulo и соавт.…”
Section: иммунотерапия базалиомыunclassified